A multidisciplinary categorization of challenges of reuse of residential buildings - Ghoz, Lamiaa (Frontiers in Sustainable Cities, 2025)
The reuse of buildings provides environmental, economic, and social benefits, offering a sustainable alternative to new construction and urban expansion. However, the multidisciplinary nature of reuse and the involvement of diverse, often conflicting interests during decision-making create significant challenges. This study aims to identify and categorize the challenges associated with the reuse of residential buildings from a multidisciplinary and global perspective. In Addition to mapping the relationships between these challenges and the scales at which they occur, addressing the research question: What are the challenges and conflicts of interest that hinder the decision-making process in the reuse of buildings? Using a semi-systematic literature review complemented by thematic analysis, this research identifies 75 sub-challenges grouped into 10 overarching themes: (1) economic viability and financial challenges, (2) building conditions, (3) design-technical challenges, (4) location challenges, (5) decision making, (6) policy and regulations, (7) knowledge, capacity, and skills, (8) culture, perception, and awareness, (9) surrounding community, and (10) timeline. The study highlights the strong interconnections between these themes, with economic and financial challenges emerging as a central factor influencing many others. Current research on building reuse often adopts a narrow disciplinary focus, lacks a global multidisciplinary perspective, and overlooks interdisciplinary connections, with limited focus on residential buildings. This paper’s originality lies in addressing these gaps by categorizing the challenges of reuse of residential buildings from multiple disciplines into a comprehensive framework, providing a resource for researchers, educators, policymakers, and practitioners to address the challenges of building reuse and informing the development of decision-support tools.